12.1k views
19 votes
Solve for x: 3(x + 1) = 2(x - 1)
0-5
What’s the answer?

User Veeti
by
4.9k points

2 Answers

4 votes
3x+3= 2(x-1)
3x+3=2x-2
3x+3-2x=-2
3x-2x=-2-3
x=-2-3 because 2+3 is five so it’s -2 so it would be - five(-5) just - turns into plus
x=-5
User MikeS
by
5.2k points
5 votes

Isolate the variable by dividing each side by factors that don't contain the variable.

Exact Form:

x=−8/3

Decimal Form:

x=−2.6

Mixed Number Form:

x=−2 2/3

hope this helps

User Yurzui
by
5.1k points